Sosialisasi Tanaman Obat Keluarga Anti Hipertensi Di Desa Kemiren, Banyuwangi - Azmi Prasasti; Nina Wijiyani; Latansa Nova Ramadhani; Hirsa Derratul Ummi (Universitas Muhammadiyah Klaten, 2024)
Hipertensi is a non-communicable disease in individuals which is characterizes by an increase in blood pressure of more than 140/90 mmHg. Controlling blood pressure and preventing complications of hypertension is influenced by several factors, including the patient’s lack of knowledge about hypertension. Medicinal plants are an important part of self-medication that can be carried out by the community to prevent hypertension. Several TOGA’s are well known as medicines for hipertension, one of which is ginger dan startfruit. This cummunity service aims to increase knowledge about hypertension and its prevention through TOGA to PKK mothers in Kemiren Village, Banyuwangi. The method is carried out through conselling and measuring the level of knowledge of hypertnesion through pre-post test result which are tested statistically using the Shapiro Wilk test. The result of the pre-post test assessment showed that the mean knowledge related to hypertension among respondents, before counseling, was 18.60 with standard deviation of 11.35. Meanwhile, ater counseling it was 87.80 with a standard deviation of 9.86. In conclusion, there was an increase in knowledge after the counseling was 4.7 times better than before the counseling